A dictionary of environmental economics, science, and policy - Grafton, R. Quentin; Pendleton, Linwood H.; Nelson, Harry W. (Cheltenham, UK ; Northampton, MA : E. Elgar Pub., 2001)
This technical dictionary serves an important need in many interdisciplinary programs. By providing definitions of many key economic terms, the dictionary can help students and practising professionals with diverse backgrounds master the language of economics and environmental sciences more easily. It also provides a basic primer on economics, international environmental problems and ecological modelling, it provides a wonderful introduction to environmental-economic models and thinking.
Includes bibliographical references.
ne 08/09/2021
Ref.
Keywords: Environmental economics; Environmental sciences